2012
DOI: 10.52041/serj.v11i2.329
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Attitudes in Statistics Education

Abstract: People forget what they do not use. But attitudes “stick.” Our article emphasizes the importance of students’ attitudes toward statistics. We examine 15 surveys that purport to assess these attitudes and then describe the Survey of Attitudes Toward Statistics, a commonly used attitude survey. We present our conceptual model of Students’ Attitudes Toward Statistics (SATS-M), which is congruent with Eccles and colleagues’ Expectancy-Value Theory (Eccles’ EVT), as well as others. The SATS-M includes three broad c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(64 citation statements)
references
References 53 publications
0
61
0
3
Order By: Relevance
“…Eccles et al (1983) agree that attitudes are made up of many dimensions; that is, attitudes consist of distinct constructs. Ramirez et al (2012) concluded a congruence between affect and EVM affective reactions and enjoyment value, cognitive competence and EVM abilities, self-concept and expectancies, value and EVM attainment and utility value, difficulty and EVM task demands perception, interest, and EVM interest value, and effort and EVM relative cost. Sorge and Schau (2002) demonstrated the usefulness of implementing this model to understand statistics success by demonstrating indirect pathways from difficulty to affect, and therefore achievement, through cognitive competence (Hood et al, 2012).…”
Section: Framework Of the Studymentioning
confidence: 95%
See 1 more Smart Citation
“…Eccles et al (1983) agree that attitudes are made up of many dimensions; that is, attitudes consist of distinct constructs. Ramirez et al (2012) concluded a congruence between affect and EVM affective reactions and enjoyment value, cognitive competence and EVM abilities, self-concept and expectancies, value and EVM attainment and utility value, difficulty and EVM task demands perception, interest, and EVM interest value, and effort and EVM relative cost. Sorge and Schau (2002) demonstrated the usefulness of implementing this model to understand statistics success by demonstrating indirect pathways from difficulty to affect, and therefore achievement, through cognitive competence (Hood et al, 2012).…”
Section: Framework Of the Studymentioning
confidence: 95%
“…In the aforementioned problem, the role of attitudes in the light of statistics courses was acknowledged (Leong, 2006). Attitudes toward statistics comprised students' affect, cognitive competence, value, difficulty, interest, and effort (Ramirez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The conceptual model underlying the SATS instruments, the SATS-M, is based primarily on Eccles's EVT and has been described as an application of EVT to statistics education (Schau, 2003a(Schau, , 2003cSorge & Schau, 2002). The most recent SATS-M also draws from self-determination theory, self-efficacy theory, and achievement goal theory (Ramirez et al, 2012). While there are compatibilities between EVT and the attitudinal components measured by the SATS instruments (Schau, 2003c), EVT did not guide the development of the SATS scales (Xu & Schau, 2019).…”
Section: Challenges With Undergraduate Introductory Studentsmentioning
confidence: 99%
“…As previously noted, the theoretical framework was not an a priori guide for the development of the SATS-28 instrument: the four-factor structure was proposed by the participants in the NGT process (Schau et al, 1995). A posteriori alignment of SATS instruments with EVT through the SATS-M framework results in important oversimplifications of Eccles's EVT (Ramirez et al, 2012). For example, the EVT model conceptualizes Value as having four components: Interest, Attainment, and Utility Value, and Cost (Eccles & Wigfield, 2002).…”
Section: Challenges With Undergraduate Introductory Studentsmentioning
confidence: 99%
See 1 more Smart Citation